If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2(0.50 + -1) = 14 Combine like terms: 0.50 + -1 = -0.5 4x + -2(-0.5) = 14 Multiply -2 * -0.5 4x + 1 = 14 Reorder the terms: 1 + 4x = 14 Solving 1 + 4x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 14 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 14 + -1 4x = 14 + -1 Combine like terms: 14 + -1 = 13 4x = 13 Divide each side by '4'. x = 3.25 Simplifying x = 3.25
| 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P | | 4m+8m=84 | | 2(m-8)=12 | | 9k(8k+7)= | | 10x+44=2(8x-23) | | T+4=120 | | 10-2x=-2y | | 77x^2-145+50= | | 9(x-7)+54=9x-8 | | 2(m-8)=54 | | 16-n=2n+8+5n | | 48+3x=246-15x | | 6x+4=1x-11 | | 7x-20=4x+30 | | 3(x+9)=60 | | 7+2x-10=x+2 | | 105+9.50r=14.75r | | 3x-3+5x-7=5x+3x+10 | | 3x-10=1x+4 | | 2(x+6)=-6x+2 | | 4(c+3t)=x | | 2(x-2)-54=7x-5(x+6) | | 5c^2+10x=0 |